Integrating Scientists into the Sports Environment: A Case Study of Gymnastics in New Zealand - Kerr, R. (Journal of Sport and Social Issues, 2012)
This article examines how sports scientists who operate outside the sports training arena are mobilized to work with gymnasts in New Zealand. Although sociology of sport has drawn attention to a variety of facets of sports science, there has been only little attention to the enrolment processes through which sports scientists become part of the sporting network. This study uses a perspective specifically developed by actor network theorists for the study of mobilization and enrolment: the"sociology of translation" (Callon). The results demonstrate how this perspective reveals the power relations within the gymnastics network and how a variety of different actors, including individuals like gymnasts and coaches, and organizations, such as the government, can determine how enrolment processes operate.